HOW BRAND TRUST MAKES PRICE AND SERVICE QUALITY SATISFY CUSTOMER INFORMATION TECHNOLOGY - Krisnanto, Umbas; Natanugraha, Fiksa Atlita (Jurnal Aplikasi Manajemen, 2023)
Customer satisfaction is an important factor in the success of an institution or company. It causes the firm to strive to provide the best service to its customers to create customer satisfaction. Customer satisfaction can be determined by the customer's perception and experience of the performance of using a product or service that can meet his expectations. Customer satisfaction will be achieved after the customer uses a product or service. The customer's wants and needs can be fulfilled and exceed his expectations. Five main things influence customer satisfaction: product quality, service quality, price, emotional factors, and the ease of obtaining the product or service. This study aims to analyze the effect of service quality, product quality, and price on customer satisfaction with brand trust as a mediating variable in information technology companies. The data in this study were processed using the Smart-PLS version 3 application. This study used a saturated sample of 450 respondents who worked for information technology company partners. Respondents filled out questionnaires using Google Forms. The results partially showed that service quality, product quality, price, and brand trust had significant and positive effects on customer satisfaction, while for the mediating effect, this study found that brand trust was able to mediate the effect of product quality on customer satisfaction but had not been able to mediate the effect between service quality on satisfaction customers and price on customer satisfaction. This research implies that information technology consumers do not buy services or products based on brand trust but on the services or products offered. Further research is needed to strengthen or weaken this phenomenon.